Family relationships and familial responses to health issues - Blair, Sampson Lee; McCormick, Jennifer Higgins (Contemporary perspectives on family research, 2014)
Around the globe, families are often faced with a variety of health issues, often as a result of social, political, religious, and economic forces. Health issues affect not only individual family members, but also impact family relationships and structures. Illnesses, injuries, and health problems can strike at any time, and can have long-lasting consequences for families. When a family members health is in jeopardy, it can bring about a wide variety of dilemmas. This multidisciplinary volume addresses the impact these issues have on the family as a unit; how they impact family relationships as well as how the family as a whole responds. The chapters cover a wide range of health related topics including illness in adults and children, sexual relationships, mental health, and disability. Through the use of a wide variety of methodological and theoretical perspectives, the family scholars in this volume provide considerable insight into the ways in which families are affected by health, as well as how they adapt to and cope with health-related dilemmas.